Integration of the Tri-Centre Model in Tahfidz Learning Management: Collaboration of Schools, Families, and Tahfidz Houses - Rona Sofia Ulya; Fatkurroji; Mustaqim (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to analyse the effectiveness of the Tri-Centre Model in Tahfidz learning, which involves the collaboration between schools, families, and Tahfidz houses. The primary focus of this research is to understand how these three elements work together to improve students' Qur'anic memorisation achievements at SD Muhammadiyah Pati and SD IT Nur Madinah. This study employs a qualitative approach with a multi-case study method. Data were collected through in-depth interviews, participatory observation, and document analysis involving school principals, Tahfidz coordinators, Tahfidz teachers, parents, and Tahfidz house managers over a period of five months. The findings indicate that collaboration among schools, families, and Tahfidz houses has a positive impact on enhancing students' Qur'anic memorisation. At SD Muhammadiyah Pati, students meet the target of memorising one Juz per year, while at SD IT Nur Madinah, the target is 3–4 Juz. Parental involvement in muroja'ah (review) activities at home greatly supports the consistency of students' memorisation. However, challenges such as students’ time constraints and the lack of formal coordination among the educational elements need to be addressed to maximise the effectiveness of this model. This study contributes by providing insights into the importance of collaboration between schools, families, and Tahfidz houses in enhancing Tahfidz learning. However, this research is limited to two schools in Pati District, and its findings may not be fully generalizable. Recommendations for future research include expanding the sample size and employing quantitative methods to gather more comprehensive data, as well as exploring ways to enhance communication among the three educational elements.